Liquid crystal alignment agent, method for producing the same, liquid crystal alignment film, and liquid crystal display element
By using the polyimide precursor imide obtained by polycondensation reaction of tetracarboxylic acid dianhydride and diamine with a specific structure as the liquid crystal alignment agent, the problem of the influence of light irradiation in the photo-oriented method is solved, and high-performance liquid crystal is achieved The manufacturing of the orientation film improves the afterimage characteristics and production efficiency of the liquid crystal representation element.
Patent Information
- Application Number
- CN201980055005.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-20
- Filing Date
- 2019-08-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2039-08-19
AI Technical Summary
The photo-oriented method has problems in the liquid crystal representation element that the amount of light irradiation affects energy cost and production speed. At the same time, the obtained liquid crystal orientation film has insufficient residual characteristics, which makes it difficult to meet the needs of high-performance liquid crystal displays.
The polyimide precursor imide obtained by polycondensation reaction of a specific tetracarboxylic acid dianhydride or its derivatives with a specific diamine is used as the liquid crystal alignment agent, and polarized ultraviolet rays are treated by reducing the amount of light irradiation to form a good residue. A liquid crystal alignment film with shadow characteristics.
It is achieved that good liquid crystal alignment capability and stable liquid crystal alignment film are obtained while reducing the amount of light irradiation, and the manufacturing process is reduced, and the yield of the liquid crystal display element and the afterimage characteristics caused by AC drive are improved.
Smart Images

Figure CN112602013B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid crystal aligning agent, a method for producing the same, a liquid crystal aligning film obtained therefrom, and a liquid crystal display element including the obtained liquid crystal aligning film. Background Art
[0002] Liquid crystal display elements used in liquid crystal televisions, liquid crystal displays, etc. are usually provided with a liquid crystal alignment film for controlling the alignment state of liquid crystals. The most popular liquid crystal alignment film in industry is currently produced by rubbing the surface of a film formed on an electrode substrate and formed of polyamic acid and / or polyimide imidized therefrom in one direction with a cloth such as cotton, nylon, polyester, etc., so-called brushing.
[0003] Brushing treatment is a simple and industrially useful method with excellent productivity. However, with the high performance, high precision and large size of liquid crystal display elements, various problems such as scratches on the surface of the alignment film, dust generation, mechanical force, static electricity, and unevenness in the surface of the alignment treatment caused by brushing treatment have become obvious. As a method to replace brushing treatment, the following photo-orientation method is known: by irradiating polarized ultraviolet rays, the liquid crystal orientation ability is given. In the liquid crystal orientation treatment based on the photo-orientation method, the following methods are proposed: treatment using photoisomerization reaction, treatment using photocrosslinking reaction, treatment using photodecomposition reaction, etc.
[0004] Patent Document 1 proposes the following scheme: a polyimide film having an alicyclic structure such as a cyclobutane ring on the main chain is used in a photo-alignment method. Compared with the brushing treatment method, the photo-alignment method can improve the contrast and viewing angle characteristics of the liquid crystal display element of the IPS drive mode and the FFS drive mode (boundary electric field switching), and therefore, it has attracted much attention as a promising liquid crystal alignment treatment method.
[0005] In the liquid crystal alignment film used in the liquid crystal display element of the IPS drive mode and the FFS drive mode, on the basis of the excellent basic characteristics such as liquid crystal orientation and electrical characteristics, an orientation restriction force is required to suppress the residual image caused by long-term driving, but the liquid crystal alignment film obtained by the photo-orientation method has a problem of weak orientation restriction force compared with the liquid crystal alignment film obtained by the brushing treatment. In addition, in the liquid crystal alignment film obtained by the photodecomposition reaction, the low molecular weight component generated by the photodecomposition becomes the cause of reducing the orientation restriction force, and a method of removing the low molecular weight component by heating treatment and cleaning treatment is proposed (Patent Document 2).
[0006] However, in the manufacture of liquid crystal display elements, in order to remove low molecular weight components, additional heating treatment steps and cleaning treatment steps are required, which leads to an increase in the manufacturing steps of liquid crystal display elements. In contrast, the following method for manufacturing a liquid crystal alignment film is proposed: even with a small number of steps, it is possible to suppress the residual image caused by long-term driving, and there is no adverse condition caused by low molecular weight components (Patent Document 3).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 9-297313
[0010] Patent Document 2: Japanese Patent Application Publication No. 2011-107266
[0011] Patent Document 3: WO2018 / 117239 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] When the alignment treatment is performed by the photo-alignment method, the light irradiation amount becomes a factor that affects the energy cost and the production speed. Therefore, it is preferred to perform the alignment treatment with a small irradiation amount. However, even if it is a liquid crystal alignment agent that can obtain good afterimage characteristics, when the light irradiation amount is reduced, there is still a problem of insufficient afterimage characteristics.
[0014] Therefore, the object of the present invention is to provide: a liquid crystal alignment agent that can obtain good afterimage characteristics and good quality and stable liquid crystal orientation capabilities even if the amount of light irradiation in the orientation treatment based on the photo-orientation method is reduced, a manufacturing method thereof, a liquid crystal alignment film obtained therefrom, and a liquid crystal display element having the obtained liquid crystal alignment film.
[0015] Solutions for solving problems
[0016] The present inventors have conducted intensive studies to achieve the above-mentioned object, and as a result, have found that the above-mentioned object can be achieved by the present invention having the following gist.
[0017] A liquid crystal alignment agent, characterized in that it contains a polyimide, wherein the polyimide is an imide of a polyimide precursor obtained by a condensation reaction of a tetracarboxylic acid component containing tetracarboxylic dianhydride or a derivative thereof represented by the following formula (1) and a diamine component containing a first diamine represented by the following formula (3) and a second diamine represented by the following formula (4).
[0018]
[0019] Among them, in formula (1), X1 It is a structure represented by the following formula (X1-1) or (X1-2).
[0020]
[0021] Among them, in formula (X1-1) and (X1-2), R 3 ~R 12 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms containing a fluorine atom, or a phenyl group, 3 ~R 6 At least one of them is a group other than a hydrogen atom in the above definition.
[0022]
[0023] Among them, in formula (3), A 1 is an alkylene group having 2 to 10 carbon atoms, or a -CH 2 - is replaced by -O- or -S- under discontinuous conditions. 2 is a halogen atom, a hydroxyl group, an amino group, a mercapto group, a nitro group, a phosphate group, or a monovalent organic group having 1 to 20 carbon atoms, a is an integer of 0 to 4, and there are multiple A 2 In the case of A 2 b and c are each independently an integer of 1 or 2, and d is an integer of 0 or 1.
[0024]
[0025] Effects of the Invention
[0026] By using the liquid crystal alignment agent of the present invention, it is possible to significantly reduce the amount of light irradiation, and a liquid crystal alignment film with good afterimage characteristics can be obtained. In addition, the liquid crystal alignment film obtained by the liquid crystal alignment agent of the present invention has a high yield in the manufacture of liquid crystal panels, and can reduce the afterimage caused by AC drive generated in the liquid crystal display element of the IPS drive mode and the FFS drive mode, and can obtain the IPS drive mode and the FFS drive mode liquid crystal display element with excellent afterimage characteristics. DETAILED DESCRIPTION
[0027] The liquid crystal aligning agent of the present invention is characterized in that it contains a polyimide (hereinafter also referred to as a specific polymer), which is an imide of a polyimide precursor obtained by a condensation reaction of a tetracarboxylic acid component containing tetracarboxylic dianhydride or its derivative having a specific structure (hereinafter also referred to as a tetracarboxylic acid component) and a diamine component containing two diamines having a specific structure (hereinafter also referred to as a diamine component).
[0028] <Specific polymers>
[0029] The specific polymer used in the present invention is a polyimide of an imide product of a polyimide precursor with a specific structure. As a polyimide precursor, there is no particular limitation as long as it is a polyimide precursor that forms an imide ring by chemical imidization using heating or a catalyst. From the viewpoint of imidization using heating or chemical imidization being easy to carry out, as a polyimide precursor, preferably polyamic acid or polyamic acid ester.
[0030] The imidization ratio of the polyimide is not particularly limited, but is preferably 10 to 100%, more preferably 50 to 100%, and further preferably 50 to 80%.
[0031] Hereinafter, each component serving as a raw material for obtaining the above-mentioned specific polymer will be described in detail.
[0032] <Tetracarboxylic acid derivative ingredient>
[0033] As the tetracarboxylic acid component used for polymerization of the specific polymer used for the liquid crystal aligning agent of the present invention, not only tetracarboxylic dianhydride but also tetracarboxylic acid, tetracarboxylic dihalide, tetracarboxylic acid dialkyl ester, or tetracarboxylic acid dialkyl ester dihalide and the like which are derivatives thereof can be used.
[0034] The tetracarboxylic dianhydride or a derivative thereof is preferably one represented by the following formula (1).
[0035]
[0036] Among them, X 1 It is a structure represented by the following formula (X1-1) or (X1-2).
[0037]
[0038] Among them, R 3 ~R 12 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms and containing a fluorine atom, or a phenyl group. 3 ~R 6 At least one of them is a group other than a hydrogen atom in the above definition.
[0039] From the perspective of liquid crystal orientation, X 1 The above formula (X1-1) is preferred, at least one selected from the following formulas (X1-1-1) to (X1-1-5) is more preferred, and the following formula (X1-1-1) is particularly preferred. The tetracarboxylic dianhydride or its derivative represented by formula (1) may be used in combination of two or more.
[0040]
[0041] The usage ratio of the tetracarboxylic dianhydride or its derivative represented by the above formula (1) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, based on 1 mol of all tetracarboxylic acid components used in the specific polymer.
[0042] In addition, in the case where the tetracarboxylic acid component used in the polymerization of the specific polymer described in the present invention further contains tetracarboxylic dianhydride or a derivative thereof represented by the following formula (2), in addition to the tetracarboxylic dianhydride or a derivative thereof represented by the above formula (1), it is more preferred from the viewpoint of suppressing bright spots generated by decomposition products and liquid crystal orientation.
[0043]
[0044] Among them, X 2 Selected from the following formulas (X2-1) to (X2-6).
[0045]
[0046] Among them, X 2 The above formula (X2-1), (X2-5) or (X2-6) is preferred, and the formula (X2-1) is particularly preferred. The tetracarboxylic dianhydride represented by the formula (2) and its derivatives may be used in combination of two or more.
[0047] The usage ratio of the tetracarboxylic dianhydride or its derivative represented by the above formula (2) is preferably 1 to 30 mol%, more preferably 10 to 30%, and further preferably 10 to 20%, based on 1 mol of all tetracarboxylic acid components used in the specific polymer.
[0048] The tetracarboxylic dianhydride component used for polymerization of the specific polymer described in the present invention may contain tetracarboxylic dianhydride other than those represented by the above formulae (1) and (2) and derivatives thereof.
[0049] <Diamine>
[0050] The diamine component used for polymerization of the specific polymer used for the liquid crystal aligning agent of the present invention contains at least one first diamine selected from diamines represented by the following formula (3) and at least one second diamine selected from diamines represented by the following formula (4).
[0051]
[0052] Among them, A 1 is an alkylene group having 2 to 10 carbon atoms, or a -CH 2 - is replaced by -O- or -S- under discontinuous conditions.2 Each is independently a halogen atom, a hydroxyl group, an amino group, a mercapto group, a nitro group, a phosphoric acid group, or a monovalent organic group having 1 to 20 carbon atoms. a is an integer of 0 to 4, and there may be a plurality of A 2 In the case of A 2 b and c are each independently an integer of 1 or 2, and d is 0 or 1.
[0053]
[0054] Preferred specific examples of the first diamine represented by formula (3) are listed below, but the present invention is not limited thereto. Among them, formula (3-1), (3-3), (3-5) to (3-7) or (3-12) are particularly preferred. The first diamine represented by formula (3) may be used in combination of two or more.
[0055]
[0056] The content of the first diamine represented by formula (3) is preferably 40 to 90 mol%, more preferably 40 to 75 mol%, based on the total diamine components used in the specific polymer.
[0057] Preferred specific examples of the second diamine represented by formula (4) are given below, but the present invention is not limited to these.
[0058] The second diamine represented by formula (4) may be used in combination of two or more.
[0059]
[0060] The content of the second diamine represented by formula (4) is preferably 10 to 40 mol%, more preferably 20 to 40 mol%, based on the total diamine components used in the specific polymer.
[0061] The diamine component used for polymerization of the specific polymer contained in the liquid crystal aligning agent of this invention may contain diamines other than the said 1st diamine and 2nd diamine (henceforth also called other diamine).
[0062] Although examples of other diamines are given below, the present invention is not limited to these.
[0063] m-phenylenediamine, 4-(2-(methylamino)ethyl)aniline, 3,5-diaminobenzoic acid, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 3,3'-diaminobenzophenone, 1,4-diaminonaphthalene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-aminophenyl)propane, 1,3-bis(4-aminophenethyl)urea, etc.
[0064] In addition, from the viewpoint of improving the solvent solubility of polyimide and making it easier for the specific polymer component to be unevenly present near the surface layer of the liquid crystal alignment film when the liquid crystal aligning agent of the present invention contains a polymer other than the specific polymer, it is preferred to use at least one of the diamines represented by the following formula (5) as the other diamine.
[0065] H 2 NY 1 -NH 2 (5)
[0066] Among them, in formula (5), Y 1 It is a divalent organic group having a structure represented by the following formula (6).
[0067]
[0068] In formula (6), D represents a protecting group which is substituted with a hydrogen atom by heating, and * represents a linking site with another structure. A preferred structure of D is tert-butoxycarbonyl.
[0069] Preferred specific examples of the diamine represented by formula (5) are given below, but the present invention is not limited to these. In addition, Boc in the following structure represents a tert-butoxycarbonyl group.
[0070]
[0071] When the diamine represented by the formula (5) is used, the diamine represented by the formula (5) is preferably contained in an amount of 5 to 30 mol % based on the total amount of diamine components used in the specific polymer.
[0072] <Production method of polyamic acid ester, polyamic acid, and polyimide>
[0073] The polyamic acid ester and the polyamic acid which are the polyimide precursors used in the present invention, and the polyimide which are imidates of these polyimide precursors can be synthesized by a known method. As an example thereof, the method described in WO2013 / 157586 can be cited.
[0074] The molecular weight of the specific polymer is not particularly limited as long as a good coating film can be formed, and for example, the weight average molecular weight (hereinafter, also referred to as Mw) is preferably 2,000 to 500,000, more preferably 5,000 to 300,000, and further preferably 10,000 to 100,000. In addition, the number average molecular weight (hereinafter, also referred to as Mn) is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and further preferably 5,000 to 50,000.
[0075] <Liquid crystal alignment agent>
[0076] The liquid crystal aligning agent of the present invention is a composition containing the above-mentioned specific polymer and an organic solvent, and may contain two or more specific polymers of different structures. In addition, the liquid crystal aligning agent of the present invention may contain a polymer other than the specific polymer (hereinafter also referred to as a second polymer) and various additives.
[0077] When the liquid crystal aligning agent of the present invention contains the second polymer, the ratio of the second polymer to all polymer components is preferably 5 mass % or more, and as one example thereof, 5 to 95 mass % can be mentioned.
[0078] Examples of the second polymer include polyamic acid, polyimide, polyamic acid ester, polyester, polyamide, polyurea, polyorganosiloxane, cellulose derivatives, polyacetal, polystyrene or its derivatives, poly(styrene-phenylmaleimide) derivatives, and poly(meth)acrylate.
[0079] In particular, a polyamic acid obtained from a tetracarboxylic dianhydride component and a diamine component (hereinafter, also referred to as a second polyamic acid) is preferably used as the second polymer.
[0080] As a tetracarboxylic dianhydride component for obtaining the 2nd polyamic acid, the compound represented by following formula (7) is mentioned.
[0081]
[0082] In formula (7), A is a tetravalent organic group, preferably a tetravalent organic group having 4 to 30 carbon atoms.
[0083] Preferred structures of A are shown below, but the present invention is not limited to these.
[0084]
[0085] In the above structure, from the viewpoint of further improving the light orientation, (A-1) and (A-2) are preferred, from the viewpoint of improving the relaxation rate of charge accumulation, (A-4) is preferred, and from the viewpoint of further improving the liquid crystal orientation and improving the relaxation rate of charge accumulation, (A-15) to (A-17) are preferred. The tetracarboxylic dianhydride component used to obtain the second polyamic acid may be one tetracarboxylic dianhydride, or two or more tetracarboxylic dianhydrides may be used in combination.
[0086] Examples of the diamine component for obtaining the second polyamic acid include the diamine represented by the above formula (3), the diamine represented by the above formula (4), and other diamines exemplified above.
[0087] Moreover, from the viewpoint of improving the relaxation rate of charge accumulation, it is preferable to use at least one diamine represented by the following formula (8). The diamine component for obtaining the second polyamic acid may use two or more diamines in combination.
[0088] H 2 NY 2 -NH 2 (8)
[0089] Among them, in formula (8), Y 2 It is a divalent organic group having a nitrogen atom bonded to an aromatic group or having a nitrogen-containing aromatic heterocycle.
[0090] The following shows the preferred Y 2 structures, but the present invention is not limited to these.
[0091]
[0092] The molecular weight of the second polyamic acid is not particularly limited, and for example, Mw is 2,000 to 500,000, preferably 5,000 to 300,000, and more preferably 10,000 to 100,000. Mn is 1,000 to 250,000, preferably 2,500 to 150,000, and more preferably 5,000 to 50,000.
[0093] The content (concentration) of the polymer in the liquid crystal aligning agent of the present invention can be appropriately changed by setting the thickness of the coating film to be formed. From the aspect of forming a uniform and defect-free coating film, it is preferably 1% by mass or more, and from the aspect of the storage stability of the solution, it is preferably 10% by mass or less. The concentration of the polymer is particularly preferably 2 to 8% by mass.
[0094] The organic solvent contained in the liquid crystal aligning agent of the present invention is not particularly limited as long as the polymer component is uniformly dissolved. If its specific example is listed, N, N-dimethylformamide, N, N-diethylformamide, N, N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-methylcaprolactam, 2-pyrrolidone, N-vinyl-2-pyrrolidone, dimethyl sulfoxide, dimethyl sulfone, γ-butyrolactone, 1,3-dimethyl-imidazolidinone, 3-methoxy-N, N-dimethylpropionamide, etc. can be cited. They can be used in one or mixed with two or more. In addition, in the case of a single, even if it is a solvent that cannot uniformly dissolve the polymer component, as long as it is a range in which the polymer is not precipitated, it can be mixed in the above-mentioned organic solvent.
[0095] The liquid crystal aligning agent of the present invention may also contain, in addition to the organic solvent for dissolving the polymer component, a solvent for improving the uniformity of the coating film when the liquid crystal aligning agent is applied to the substrate. The above-mentioned solvent generally uses a solvent having a surface tension lower than that of the above-mentioned organic solvent. As a specific example thereof, ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, ethyl carbitol acetate, ethylene glycol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 1-butoxy-2-propanol, 1-phenoxy-2-propanol, propylene glycol monoacetate, propylene glycol diacetate, propylene glycol-1-monomethyl ether-2-acetate, propylene glycol-1-monoethyl ether-2-acetate, butyl cellosolve acetate, dipropylene glycol, 2-(2-ethoxypropoxy) propanol, methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, isoamyl lactate, etc., may be cited. These solvents may be used in combination of two or more.
[0096] In addition to the above, the liquid crystal alignment agent of the present invention may further include: a dielectric or conductive material for the purpose of changing the electrical properties of the liquid crystal alignment film, such as the dielectric constant and conductivity; a silane coupling agent for the purpose of improving the adhesion between the liquid crystal alignment film and the substrate; a crosslinking compound for the purpose of increasing the hardness and density of the film when the liquid crystal alignment film is formed; and an imidization accelerator for the purpose of efficiently performing the imidization of the polyamic acid when the coating is fired.
[0097] <Method for producing liquid crystal alignment film>
[0098] Although the manufacturing method of the liquid crystal aligning film using the liquid crystal aligning agent of this invention is not specifically limited, By manufacturing it by the process (A) - (D) shown below, the excellent characteristics which the liquid crystal aligning agent of this invention has can be demonstrated more effectively.
[0099] Step (A): A step of applying the liquid crystal aligning agent of the present invention on a substrate.
[0100] Step (B): A step of obtaining a film by heating the applied liquid crystal aligning agent at a temperature at which thermal imidization does not substantially proceed.
[0101] Step (C): a step of irradiating the film obtained in step (B) with polarized ultraviolet rays.
[0102] Step (D): a step of calcining the film obtained in step (C) at a temperature of 100° C. or higher and higher than that in step (B).
[0103] Hereinafter, each step (A) to (D) will be described in more detail.
[0104] <Process (A)>
[0105] As the substrate for coating the liquid crystal aligning agent of the present invention, there is no particular limitation as long as it is a substrate with high transparency, and a glass substrate, a silicon nitride substrate, an acrylic substrate, a plastic substrate such as a polycarbonate substrate, etc. can be used. At this time, from the aspect of simplifying the process, it is preferred to use a substrate formed with an ITO electrode for driving the liquid crystal. In addition, in a reflective liquid crystal display element, if only a single-sided substrate is formed, an opaque substance such as a silicon wafer can also be used, and the electrode at this time can also use a material that reflects light such as aluminum.
[0106] The coating method of the liquid crystal aligning agent is not particularly limited, and is generally performed by screen printing, offset printing, flexographic printing, or inkjet method, etc. Other coating methods include dipping, roll coater, slit coater, spinning machine, spraying, etc., and they can be used according to the purpose.
[0107] <Process (B)>
[0108] Step (B) is a step of heating the liquid crystal alignment agent applied to the substrate to form a film without substantially performing thermal imidization. After the liquid crystal alignment agent is applied to the substrate, the solvent is evaporated to form a film by heating means such as a hot plate, a thermal cycle oven, an IR (infrared) oven, etc. In this step, as long as the organic solvent contained in the liquid crystal alignment agent can be removed without substantially performing thermal imidization, any temperature and time can be selected. Usually, in order to fully remove the contained solvent, it is preferably heated at 50 to 150°C for 1 to 10 minutes, and more preferably heated at 50 to 120°C for 1 to 5 minutes.
[0109] <Process (C)>
[0110] Step (C) is a step of irradiating the film obtained in step (B) with polarized ultraviolet rays. The ultraviolet rays preferably have a wavelength of 200 to 400 nm, and more preferably have a wavelength of 200 to 300 nm. In order to improve the liquid crystal orientation, the substrate coated with the liquid crystal orientation agent may be heated at 50 to 250°C while being irradiated with ultraviolet rays. The irradiation amount of ultraviolet rays is, for example, 1 to 2000 mJ / cm 2 , preferably 10 to 1000 mJ / cm 2 , more preferably 100 to 600 mJ / cm 2 In addition, the higher the extinction ratio of polarized ultraviolet light is, the higher anisotropy can be imparted, which is preferred. Specifically, the extinction ratio of linearly polarized ultraviolet light is preferably 10:1 or more, and more preferably 20:1 or more.
[0111] <Process (D)>
[0112] Process (D) is a process for firing the film irradiated with ultraviolet rays in process (C). Specifically, it is a process for firing at a temperature above 100°C and higher than the temperature heated in process (B). The firing temperature is not particularly limited as long as it is above 100°C and higher than the heating temperature in process (B), and is preferably 150 to 300°C, more preferably 150 to 250°C, and further preferably 200 to 250°C. The firing time is preferably 5 to 120 minutes, more preferably 5 to 60 minutes, and further preferably 5 to 30 minutes. If the thickness of the liquid crystal alignment film after firing is too thin, the reliability of the liquid crystal display element is sometimes reduced, therefore, preferably 5 to 300nm, more preferably 10 to 200nm.
[0113] The liquid crystal alignment film of the present invention is suitable as a liquid crystal alignment film of a liquid crystal display element of a transverse electric field mode such as an IPS mode and an FFS mode, and is particularly useful as a liquid crystal alignment film of a liquid crystal display element of an FFS mode. The liquid crystal display element can be prepared as follows: after obtaining a substrate with a liquid crystal alignment film obtained from the liquid crystal alignment agent of the present invention, a liquid crystal cell is prepared by a known method, and the liquid crystal cell is used to prepare the liquid crystal display element.
[0114] As an example of a method for producing a liquid crystal unit, a liquid crystal display element with a passive matrix structure is described as an example. It should be noted that a liquid crystal display element with an active matrix structure in which a switching element such as a TFT (Thin Film Transistor) is provided in each pixel portion constituting an image display may be used.
[0115] Specifically, transparent glass substrates are prepared, a common electrode is provided on one substrate, and segment electrodes are provided on the other substrate. These electrodes can be formed into ITO electrodes, for example, and patterned in a manner that enables the desired image to be displayed. Next, an insulating film is provided on each substrate so as to cover the common electrode and the segment electrodes. The insulating film can be made of, for example, SiO formed by a sol-gel method. 2 -TiO 2 membrane.
[0116] Next, a liquid crystal alignment film is formed on each substrate, one substrate is overlapped with another substrate, so that the liquid crystal alignment films of each other face each other, and the periphery is bonded with a sealant. In order to control the substrate gap, it is usually preferred to mix spacers in the sealant in advance. In addition, it is preferred to spread spacers for substrate gap control in the surface part where the sealant is not set. An opening that can be filled with liquid crystal from the outside is set in advance in a part of the sealant. Next, a liquid crystal material is injected into the space surrounded by the two substrates and the sealant through the opening set in the sealant, and then the opening is sealed with an adhesive. The injection can use a vacuum injection method or a method using capillary phenomena in the atmosphere. The liquid crystal material can use any of a positive liquid crystal material and a negative liquid crystal material. Next, a polarizer is set. Specifically, a pair of polarizers are adhered to the surface opposite to the liquid crystal layer of the two substrates.
[0117] As described above, by using the liquid crystal alignment agent of the present invention, the following liquid crystal alignment film can be obtained: it can suppress the afterimage caused by long-term AC driving in the liquid crystal display elements of IPS driving mode and FFS driving mode, and there are no adverse conditions such as bright spots caused by residual low molecular weight compounds, and it can be manufactured with fewer steps than before.
[0118] Example
[0119] The present invention will be described in more detail below with reference to Examples, but the present invention is not to be construed as being limitative thereof.
[0120] It should be noted that the abbreviations of the compounds and the methods for measuring the properties are as follows. In addition, the numerical values and units in the following are based on mass unless otherwise specified.
[0121] NMP: N-methyl-2-pyrrolidone, GBL: γ-butyrolactone,
[0122] BCS: Butyl Cellosolve,
[0123]
[0124]
[0125] [Viscosity]
[0126] The viscosity was measured using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) at a sample volume of 1.1 mL, a conical rotor TE-1 (1°34', R24), and a temperature of 25°C.
[0127] [Molecular weight]
[0128] The Mn and Mw were calculated by measuring using a GPC (normal temperature gel permeation chromatography) apparatus as polyethylene glycol or polyethylene oxide equivalent values.
[0129] GPC apparatus: Shodex (GPC-101), column: Shodex (KD803, KD805 in series), column temperature: 50°C, eluent: N,N-dimethylformamide (lithium bromide monohydrate (LiBr·H 2 O) is 30 mmol / L, phosphoric acid anhydrous crystals (orthophosphoric acid) is 30 mmol / L, tetrahydrofuran (THF) is 10 ml / L), flow rate: 1.0 ml / min
[0130] Standard samples for preparing the calibration curve: TSK standard polyethylene oxide (Mw: about 900000, 150000, 100000, 30000) manufactured by Tosoh Corporation, and polyethylene glycol (peak top molecular weight (Mp) about 12000, 4000, 1000) manufactured by Polymer Laboratories Limited. In the measurement, in order to avoid peak overlap, a mixture of four samples of 900000, 100000, 12000, 1000, and two samples of a mixture of three samples of 150000, 30000, 4000 were measured.
[0131] <Measurement of Imidization Ratio>
[0132] 20 mg of polyimide powder was placed in an NMR sample tube (NMR standard sample tube, φ5 (manufactured by Kusano Scientific Co., Ltd.)), and a mixture of deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) (0.53 ml) was added, and ultrasonic waves were applied to completely dissolve the mixture. The solution was measured for proton NMR at 500 MHz using an NMR measuring instrument (JNW-ECA500) (manufactured by JEOL DATUM LTD.). The imidization rate was determined as follows: a proton derived from a structure that did not change before and after imidization was determined as a reference proton, and the peak cumulative value of the proton derived from the NH group of the amic acid appearing in the vicinity of 9.5 ppm to 10.0 ppm was used to determine the rate of imidization using the following formula.
[0133] Imidization rate (%) = (1-α·x / y) × 100
[0134] In the above formula, x is the peak cumulative value of protons derived from the NH group of the amic acid, y is the peak cumulative value of the reference proton, and α is the ratio of the reference proton to the number of protons per NH group of the amic acid in the case of polyamic acid (imidation ratio 0%).
[0135] [Configuration of FFS-driven liquid crystal unit]
[0136] In the liquid crystal unit for the Fringe Field Switching (FFS) mode, a first glass substrate having a FOP (Finger on Plate) electrode layer composed of a common electrode-insulating layer-comb-shaped pixel electrode in a planar shape formed on the surface, and a second glass substrate having a columnar spacer with a height of 4 μm on the surface and an ITO film for antistatic formed on the back surface are formed as a set. The pixel electrode has a comb-shaped shape in which a plurality of electrode elements with a width of 3 μm are arranged in parallel at intervals of 6 μm, and one pixel has a first region and a second region with a line connecting the bent portions of the plurality of electrode elements as a boundary.
[0137] It should be noted that the liquid crystal orientation film formed on the first glass substrate is oriented in a manner such that the direction of the inner angle of the pixel bending portion is equally divided is orthogonal to the orientation direction of the liquid crystal, and the liquid crystal orientation film formed on the second glass substrate is oriented in a manner such that the orientation direction of the liquid crystal on the first substrate is consistent with the orientation direction of the liquid crystal on the second substrate when the liquid crystal unit is manufactured.
[0138] On each surface of the above-mentioned set of glass substrates, a liquid crystal alignment agent filtered with a filter having an aperture of 1.0 μm was applied by spin coating, and dried on a hot plate at 80° C. for 2 minutes. Thereafter, a predetermined amount of linearly polarized ultraviolet rays with an extinction ratio of 26:1 and a wavelength of 254 nm was irradiated to the coating surface through a polarizing plate, and then fired in a hot air circulation oven at 230° C. for 30 minutes to obtain a substrate with a liquid crystal alignment film having a film thickness of 100 nm.
[0139] Next, a sealant was printed on one of the above-mentioned glass substrates with a liquid crystal alignment film, and the other substrate was laminated in a face-to-face manner with the liquid crystal alignment film surface, and the sealant was cured to produce an empty cell. Liquid crystal MLC-3019 (Merck Co., Ltd.) was injected into the empty cell by a reduced pressure injection method, and the injection port was sealed to obtain an FFS-driven liquid crystal cell. Thereafter, the obtained liquid crystal cell was heated at 120°C for 1 hour, and after being left overnight, the afterimage characteristics were evaluated.
[0140] [Evaluation of image sticking characteristics caused by long-term AC driving]
[0141] The FFS-driven liquid crystal cell prepared above was subjected to an AC voltage of ±5 V at a frequency of 60 Hz for 120 hours in a constant temperature environment of 60° C. Thereafter, the pixel electrode and the counter electrode of the liquid crystal cell were short-circuited and left at room temperature for one day.
[0142] Regarding the liquid crystal cell subjected to the above-described process, the deviation between the alignment direction of the liquid crystal in the first region of the pixel and the alignment direction of the liquid crystal in the second region in a state where no voltage is applied is calculated as an angle.
[0143] Specifically, a liquid crystal unit is set between two polarizing plates arranged in a manner such that the polarization axes are orthogonal, the backlight is turned on, and the configuration angle of the liquid crystal unit is adjusted in such a way that the transmitted light intensity of the first area of the pixel is minimized. Then, the rotation angle required to rotate the liquid crystal unit in such a way that the transmitted light intensity of the second area of the pixel is minimized is calculated.
[0144] The smaller the value of the rotation angle is, the better the image sticking characteristics due to long-term AC driving are. When the value of the angle Δ of the liquid crystal cell is 0.1° or less, it is evaluated as "good".
[0145] Hereinafter, synthesis examples of polyamic acid and polyimide are shown.
[0146] <Synthesis example 1>
[0147] In a 300 mL four-necked flask equipped with a stirrer and a nitrogen inlet tube, 5.86 g (24.0 mmol) of DA-1, 1.73 g (16.0 mmol) of DA-2, 7.02 g (24.0 mmol) of DA-3, and 3.80 g (16.0 mmol) of DA-5 were weighed, and 205.7 g of NMP was added, and stirred while nitrogen was introduced to dissolve. While stirring the diamine solution, 14.88 g (66.4 mmol) of CA-1 and 3.00 g (12.0 mmol) of CA-2 were added, and stirred at 40° C. for 24 hours to obtain a polyamic acid solution (A-1) (viscosity: 445 mPa·s). The Mn of the polyamic acid was 11200 and the Mw was 33900.
[0148] <Synthesis Examples 2 to 7>
[0149] The same operation as in Synthesis Example 1 was carried out on the diamine component and the tetracarboxylic acid component shown in Table 1 below to obtain polyamic acid solutions (A-2) to (A-5) and (B-1) to (B-2) shown in Table 1 below. The viscosity, Mn, and Mw of the obtained polyamic acid are shown in Table 1 below.
[0150] In addition, the concentration of the polyamic acid in the polyamic acid solution obtained in Synthesis Examples 1 to 7 was 15 mass %.
[0151] [Table 1]
[0152]
[0153] <Synthesis example 8>
[0154] In a 300mL four-necked flask with a stirring device and a nitrogen inlet tube, 100g of the obtained polyamic acid solution (A-1) was measured, 50g of NMP was added, and stirred for 30 minutes. In the obtained polyamic acid solution, 16.78g of acetic anhydride and 5.20g of pyridine were added, and heated at 50°C for 3 hours to carry out chemical imidization. The obtained reaction solution was put into 600ml of methanol while stirring, and the precipitate was filtered to obtain the precipitated precipitate. The same operation was performed twice, and the resin powder was washed, and dried at 60°C for 12 hours to obtain a polyimide resin powder. The imidization rate of the polyimide resin powder was 71%, Mn=12600, Mw=33900. 3.60 g of the obtained polyimide resin powder was placed in a 100 ml Erlenmeyer flask, 26.4 g of NMP was added so that the solid content concentration became 12%, and the mixture was stirred at 70°C for 24 hours to dissolve the mixture, thereby obtaining a polyimide solution (A-1-PI) (see Table 2 below).
[0155] In addition, in Table 2, the concentration (%) under the imidization conditions represents the polymer concentration in the solution during the imidization reaction.
[0156] <Synthesis Examples 8 to 12>
[0157] Polyimide solutions (A-2-PI) to (A-5-PI) were obtained by chemical imidization in the same manner as in Synthesis Example 8, except that acetic anhydride and pyridine shown in Table 2 were used, and polyamic acid solutions (A-2) to (A-5) were used instead of polyamic acid solution (A-1). The imidization ratio and Mn / Mw of the obtained polyimide are shown in Table 2.
[0158] [Table 2]
[0159]
[0160] <Example 1>
[0161] 4.0 g of the 12% by mass polyimide acid solution (A-1-PI) obtained in Synthesis Example 8 and 4.8 g of the 15% by mass polyamic acid solution (B-1) obtained in Synthesis Example 6 were taken into a 50 ml conical flask, 3.24 g of NMP, 3.96 g of GBL, and 4.00 g of BCS were added, and mixed at 25° C. for 8 hours to obtain a liquid crystal aligning agent (1) (see Table 3 below). No abnormalities such as turbidity and precipitation were observed in the liquid crystal aligning agent, and it was confirmed to be a uniform solution.
[0162] In addition, in Table 3, A / B shows the mass % ratio of a polyimide solution / polyamic acid solution, and the solid content ratio (mass %) shows the content ratio of the polymer in a liquid crystal aligning agent.
[0163] <Examples 2 to 6, Comparative Example 1>
[0164] Liquid crystal aligning agents (2) to (8) were obtained in the same manner as in Example 1 except that the polyamic acid solution and the polyimide solution in Table 3 were used. These liquid crystal aligning agents showed no abnormalities such as turbidity and precipitation, and were confirmed to be uniform solutions.
[0165] [Table 3]
[0166]
[0167] <Example 11>
[0168] The afterimage characteristics were evaluated according to the above-mentioned [Evaluation of afterimage caused by long-term AC drive]. That is, the liquid crystal alignment agent (1) obtained in Example 1 was filtered with a filter with a pore size of 1.0 μm, and then applied to the prepared substrate with electrodes and a glass substrate with an ITO film formed on the back and a columnar spacer with a height of 4 μm by spin coating. After drying on a hot plate at 80°C for 2 minutes, the coating surface was irradiated with ultraviolet rays of a wavelength of 254 nm with a linear polarization of an extinction ratio of 26:1 through a polarizing plate, and then calcined in a hot air circulation oven at 230°C for 30 minutes to obtain a substrate with a liquid crystal alignment film having a film thickness of 100 nm.
[0169] The above two substrates were used as a set, and a sealant was printed on the substrate. After the other substrate was laminated with the liquid crystal alignment film surface facing each other and the orientation direction being 0°, the sealant was cured to make an empty cell. Liquid crystal MLC-3019 (Merck Co., Ltd.) was injected into the empty cell by the reduced pressure injection method, and the injection port was sealed to obtain an FFS driven liquid crystal cell. After that, the obtained liquid crystal cell was heated at 120°C for 1 hour, left overnight, and the residual image evaluation caused by long-term AC drive was carried out.
[0170] The value (°) of the angle Δ of the liquid crystal unit after long-term AC driving is shown in Table 4 below. That is, the irradiation amount of the ultraviolet light is 0.2 J / cm 2 The value of the angle Δ of the liquid crystal cell under Δ was 0.09°. The minimum value of the average separation angle Δ was 0.1° or less, and therefore, favorable liquid crystal orientation was obtained by the liquid crystal aligning agent (1).
[0171] <Examples 12 to 16 and Comparative Example 11>
[0172] In Examples 12 to 16 and Comparative Example 11, the liquid crystal aligning agents shown in Table 4 below were used instead of the liquid crystal aligning agent (1). FFS-driven liquid crystal cells were prepared in exactly the same manner as in Example 11, and image sticking evaluation was performed by long-term AC driving.
[0173] Table 4 shows the value of the angle Δ of each of Examples 12 to 16 and Comparative Example 11 after long-term AC driving.
[0174] [Table 4]
[0175]
[0176] As shown in Table 4, in Examples 11 to 16, the ultraviolet irradiation amount was 0.2 J / cm2 for providing an angle Δ (deg.) of 0.1° or less. 2 The angle Δ is optimal when the amount of polarized ultraviolet irradiation is as small as below: Since the image sticking property is good, the production time of the liquid crystal display element is excellently shortened.
[0177] Industrial Applicability
[0178] The liquid crystal aligning agent of this invention is useful for formation of the liquid crystal aligning film in the wide liquid crystal display element, such as an IPS drive system and an FFS drive system.
[0179] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2018-154227 filed on August 20, 2018 are incorporated herein as a disclosure of the specification of the present invention.
Claims
1. A liquid crystal alignment agent, characterized in that: The invention relates to a polyimide which is an imide product of a polyimide precursor obtained by a polycondensation reaction of a tetracarboxylic acid component containing tetracarboxylic dianhydride or a derivative thereof represented by the following formula (1) and a diamine component containing a first diamine represented by the following formula (3) and a second diamine represented by the following formula (4), wherein X1 is at least one selected from the following formulae (X1-1-1) to (X1-1-5), wherein A1 is an alkylene group having 2 to 10 carbon atoms, or a group obtained by discontinuously replacing at least one of -CH2- in the alkylene group with -O- or -S-; A2 is a halogen atom, a hydroxyl group, an amino group, a mercapto group, a nitro group, a phosphate group, or a monovalent organic group having 1 to 20 carbon atoms; a is an integer of 0 to 4; when there are a plurality of A2s, A2s are optionally the same or different; b and c are each independently an integer of 1 or 2; and d is an integer of 0 or 1; The first diamine represented by the above formula (3) is at least one diamine selected from the following formulas (3-1) to (3-12), 2. The liquid crystal alignment agent according to claim 1, wherein The second diamine represented by the above formula (4) is at least one diamine selected from the following formulas (4-1) to (4-3), 3. The liquid crystal aligning agent according to claim 1 or 2, wherein: The first diamine represented by the formula (3) is contained in an amount of 40 to 90 mol% based on the diamine component.
4. The liquid crystal aligning agent according to claim 1 or 2, wherein The second diamine represented by the formula (4) is contained in an amount of 10 to 40 mol% based on the diamine component.
5. The liquid crystal aligning agent according to claim 1 or 2, wherein The tetracarboxylic acid component further includes at least one selected from the group consisting of tetracarboxylic dianhydride and derivatives thereof represented by the following formula (2), wherein X2 is a structure selected from the following formulae (X2-1) to (X2-6), 6. The liquid crystal alignment agent according to claim 5, wherein: The tetracarboxylic dianhydride or a derivative thereof represented by the formula (2) is contained in an amount of 1 to 30 mol% based on the tetracarboxylic acid component. 7 . A liquid crystal aligning film obtained using the liquid crystal aligning agent according to claim 1 . A liquid crystal display element comprising the liquid crystal aligning film according to claim 7.
9. A method for producing a liquid crystal alignment film, comprising the following steps (A), (B), (C) and (D), Step (A): a step of applying the liquid crystal aligning agent according to any one of claims 1 to 6 on a substrate; Step (B): a step of heating the applied liquid crystal aligning agent under the condition that thermal imidization is not substantially performed to obtain a film; Step (C): a step of irradiating the film obtained in step (B) with polarized ultraviolet rays; Step (D): a step of calcining the film obtained in step (C) at a temperature of 100° C. or higher and higher than that in step (B).
10. The method for manufacturing a liquid crystal alignment film according to claim 9, wherein: In the step (B), heating is performed at 50°C to 150°C.
11. The method for producing a liquid crystal alignment film according to claim 9 or 10, wherein: In the step (D), the film is fired at 150 to 300°C.